Profitability and liquidity on firm value and capital structure as intervening variable - Sari, Ida Ayu Gede Dika Martami; Sedana, Ida Bagus Panji (International research journal of management, IT and social sciences, 2020)
This study aims to determine the effect of profitability and liquidity on firm value and determine the role of capital structure in mediating the effect of profitability and liquidity on firm value in the construction and building sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2013-2017. The population in this study are construction and building sub-sector companies that are listed on the Indonesia Stock Exchange and have complete financial statements for the period 2013-2017. This study uses samples with the census method. The data analysis technique used is path analysis. Profitability has a positive and significant effect on capital structure, Liquidity has a negative and significant effect on capital structure, capital structure has a positive and significant effect on firm value, profitability has a positive and significant effect on firm value, liquidity has a negative and not significant effect on firm value and capital structure is able to mediate the effect of profitability and liquidity on firm value.